Новые данные о коловратках рода Testudinella (Rotatoria, Monimotrochida) в фауне Украины - Овандер, Э.Н. (Вестник зоологии, 1979)
Four representatives of the Testudinella genus: T. caeca, T. truncata ecornis, T. patina intermedia, T. emarginula are given first for the Ukrainian SSR fauna. Among them T. caeca was known in the USSR only in the Leningrad Region, and T. truncata ecornis is first mentioned for the USSR fauna.